An Outbreak of Coronavirus Disease (COVID-19) among Healthcare Personnel in a Private Hospital Related to Delayed Detection of SARS-CoV-2 Infection Foci - Saksirisampan, Borimas; Rodsuk, Thanya; Nittayasoot, Natthaprang; Plernprom, Patchanee; Samphao, Ratchayapat; Pingkan, Paratthakorn; Jiraphongsa, Chuleeporn; Suphanchaimat, Rapeepong; Thananun, Sirima; Mungoomglang, Anek (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2020)
Healthcare personnel are front-line workers for disease prevention and control. On 6 Apr 2020, the Department of Disease Control received a notification on a cluster of healthcare personnel in a private hospital infected with coronavirus disease (COVID-19). The event was investigated and a cross-sectional study was conducted to describe the epidemiological characteristics of the cluster, including risk factors for SARS-CoV-2 infection. A confirmed COVID-19 case was a person with SARS-CoV-2 virus tested by reverse transcription polymerase chain reaction in one reference laboratory; and a probable COVID-19 case was a person who died of pneumonia in the hospital, did not tested for COVID-19, and had an epidemiological linkage to a confirmed case. Among total 2,287 healthcare personnel working at the hospital, 25 were confirmed cases (attack rate 1.1%). Although the attack rate was relatively low, the specific attack rate in the inpatient ward was high (32.4%) due to delayed outbreak detection. Analytic results suggested that attending infection prevention and control (IPC) training was a protective factor for COVID-19 (Odds ratio 0.04, 95% CI 0.00-0.64). In addition, a survey on personal protective equipment (PPE) showed that 66.7% of those conducting sputum suction/drug nebulization and 83.9% of those performing cardiopulmonary resuscitation used inappropriate PPE. Therefore, IPC training, including appropriate use of PPE, should be provided to all healthcare personnel. In addition, healthcare personnel should be alert for COVID-19 infection, and protect themselves according to the standard protocols. Routine screening of healthcare personnel should be performed during the COVID-19 epidemic.